The social basis of regional development in the North Great Plain Region - Nagy, János; Harsányi, Gergely; Jánosy, Orsolya; Harsányi, Endre; Nagy, Orsolya (Acta Agraria Debreceniensis, 2014)
It is a widely accepted practice in the European Union to break down countries into regions according to their stage of development, their cultural and economic characteristics. The basis of this methodology is the EU-conform MOTS system, which distinguishes territorial units on five levels. Besides the MOTS system, Hungary uses another system, too, which is the basis of our public administration, and whose roots go back to the times of King Saint Stephen: the county system. In Hungary, developmental decisions are taken by a county’s general assembly; at the same time, from an economic point of view the characteristics and competitive advantages of a county can be defined more precisely than those of a region. Szabolcs-Szatmár-Bereg County and Hajdu-Bihaur County may be described with completely different characteristics, albeit both of them are part of the North Great Plain Region. On a county level economically important and justified developmental areas may be mapped more precisely. Hajdu-Bihar County is the 4th most populous county in Hungary. With 80.2% of the population living in cities, the county is significantly urbanized. 2010 statistics show that the birth rate per 1,000 people in the county is practically the same as the birth rate of the country and that of the North Great Plain Region. Following the trends in developed countries, mothers now tend to give birth in an older age. Almost half (44.5%) of the children in Hajdu-Bihar County are born after their mother’s 30th birthday. The general health condition of the population of Hajdu-Bihar County can be described with various indicators. In terms of medical and hospital care no difference can be observed between regional and national data, the county’s health care does not straggle behind. In sum, with the health care system of the county, estimated life expectancy of men is higher than the regional average, and in case of women it is higher than both the regional and national average, according to the given year’s mortality. Children’s ratio among the county’s population is 15.9%, which is more than 1% over the national average. The ratio is higher in case of girls and boys alike. The income of the county’s population depends not only on labour income but also on social benefits. According to the analysis, the proportion of old-age pensioners and those receiving pension-like allowances within the whole population is somewhat lower in the county than the national average. The number of children receiving child-welfare and daytime care is prominent in the county. The number of families and children receiving child-care allowance has not changed significantly in recent years. All important elements of social benefits have increased in the last decade. The quality of life of the county’s population is largely affected by the presence (or absence) of basic infrastructure in their environment. Research conducted at the settlements of the county shows that currently the greater part of the population has access to basic public utility services which form part of everyday services. Although they affect the general quality of life, the network of roads and passenger traffic have their real significance in terms of economic development. The county’s modern, paved road-system had already been built earlier. Roads and pavements in inner-city areas have been paved up to 70%. The technical condition of roads and pavements can seriously impede the population’s mobility and it may hinder the development of certain settlements and districts.